Method for obtaining chromosomes (1973)
It is very easy to obtain chromosomes from anuran amphibians.Amphibians have very large chromosomes which can easily be seen with an ordinary microscope. The method used has been tested in the laboratory and also at collecting sites. All that is required are a few chemicals and simple equipment.